Prenatal diagnosis of noncompaction of the ventricular myocardium: A case report - Sosa Olavarría, Alberto (2020)
"Spongy cardiomyopathy" or noncompaction heart disease is a rare congenital cardiomyopathy of unknown etiology which results from a failure in embryogenesis in the evolutionary process of normal myocardial trabeculation. The characteristic echocardiographic findings of this disease consist of multiple myocardial trabeculations and deep intertrabecular recesses that communicate with the left or right ventricular cavity or both. We present a case of this cardiomyopathy that affects the right ventricle, in a fetus of 31 weeks gestation, whose mother was an asymptomatic carrier of said pathology. Prenatal ultrasound images are presented, including evaluation using the strain (myocardial deformation) technique, emphasizing the importance of the patient’s medical history, possible etiologies and differential diagnosis with other entities.